Simulation of solid-liquid flow in stirred tanks at high solid loading - Wadnerkar, Divyamaan; Utikar, Ranjeet; Tade, Moses; Pareek, Vishnu (CSIRO, 2012)
Solid liquid stirred tanks are commonly used in mineral industry for operations like concentration, leaching, adsorption, effluent treatment, etc. Hydrodynamic study is necessary to evaluate the performance of such systems. Especially, in the cases of high solid concentration, the flow field, slip velocity, turbulence and drag are significantly different from the single phase values and therefore, such studies become indispensable. In this study, the change in these parameters in the presence of solids and the effect of high solid concentration is discussed. Eulerian-eulerian multiphase modelling approach was used to simulate the solid suspension in stirred tanks. Multiple reference frame (MRF) approach was used to simulate the impeller rotation in a fully baffled tank. Simulations were conducted using commercial CFD solver ANSYS Fluent 13.0. The CFD simulations were conducted for concentration 20 wt% and the impeller speeds at the just suspension speed. The solid - liquid interaction was taken into account using modified Brucato drag model. A substantial decrease in the flow number was observed due to the presence of solids. The dampening of turbulence was evident in the impeller region where the solid concentration was the maximum. The drag was able to account the increase in drag at high turbulent intensities. The predictions in terms of the velocity profiles were found to be in reasonable agreement with the experimental data of Guida et al. (2010). The work provides an insight into the solid liquid flow in stirred tanks with high solid concentration and will be useful for applications such as carbon in leach circuit which operates at high solid loading.